The Encyclopedia of sedimentology - Fairbridge, Rhodes W. (Rhodes Whitmore) 1914-2006; Bourgeois, Joanne (Encyclopedia of earth sciences, 1978)
Scholarly work on sedimentology. Each article is signed and has a bibliography. Illustrated. Indexed.